The Essence of The Concepts Of Politics and The Political Process - Olimova Mokhinur (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
In this article, the emergence, formation and importance of the concept of the political and political process is studied scientifically theoretically. The broad meaning of the concept of politics, the importance of the issue of politics in the life of society from the first centuries BC, the participants in the political process and the theoretical foundations of this concept and the role of politics in amalag increase have been analyzed. The participants of the political process, the formation of the political culture of citizens in the amalag increase of policy were given our opinions and opinions.